Public Participation in Environmental Impact Assessment (EIA) and Major Sports Events: A Comparative Analysis of the London 2012 Olympic Games and the Rio 2007 Pan American Games - Pereira, Gisele Silva; De Conto, Suzana Maria (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2015)
<span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-GB;" lang="EN-US">This paper explores public participation in environmental impact assessment (EIA) and the decision making in the context of major sports events and their associated infrastructure in Brazil and England. The methodology is based on<span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-GB;" lang="EN-GB"> detailed case study analysis involving document analysis and interviews with key stakeholders. The results demonstrated that there is evidence that public participation within the EIA process informed the decision making and planning process for London 2012 and for the Pan American Village of the Rio 2007 Games. Finally, a practical <span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-GB;" lang="EN-US">recommendation for the Brazilian context and recommendations for further research are made. Participação pública na Avaliação de Impacto Ambiental (AIA) e megaeventos esportivos: uma análise comparativa dos Jogos Olímpicos de Londres 2012 e dos Jogos Pan Americanos do Rio 2007 - Este artigo explora a participação pública na Avaliação de Impacto Ambiental (AIA) e a tomada de decisão no contexto de megaeventos esportivos e a infraestrutura associada no Brasil e na Inglaterra. A metodologia baseia-se em estudo de caso envolvendo análise de documentos e entrevistas com atores-chave. Os resultados demonstraram que há evidência de que a participação pública integrante do processo de AIA informou a tomada de decisão e o processo de planejamento para Londres 2012 e para a Vila Pan Americana dos Jogos do Rio 2007. Finalmente, uma recomendação prática para o contexto brasileiro e recomendações para pesquisas futuras são destacadas.